2018
DOI: 10.1142/s0219887818501517
|View full text |Cite
|
Sign up to set email alerts
|

Scalar–tensor teleparallel gravity with boundary term by Noether symmetries

Abstract: In the framework of teleparallel gravity, the Friedman-Robertson-Walker cosmological model with scalar tensor theory where scalar field is non-minimally coupled to both the torsion scalar and boundary term is studied. Utilizing the Noether symmetry approach in such a theory, we obtain the explicit forms of the couplings and potential as a function the scalar field. We present some important cosmological solutions for the modified field equations using these functions getting via the Noether symmetry approach. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 145 publications
0
18
1
Order By: Relevance
“…Non-minimal scalar field couplings with the torsion and boundary term scalars have been explored in Refs. [688,487,100] with f (T ) = 0, ω(φ) = 1 21 . Starting with Refs.…”
Section: Non-minimally Coupled Scalar Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-minimal scalar field couplings with the torsion and boundary term scalars have been explored in Refs. [688,487,100] with f (T ) = 0, ω(φ) = 1 21 . Starting with Refs.…”
Section: Non-minimally Coupled Scalar Fieldsmentioning
confidence: 99%
“…Starting with Refs. [688,487], in order to simplify the Noether symmetry analysis, the following models were considered:…”
Section: Non-minimally Coupled Scalar Fieldsmentioning
confidence: 99%
“…In the teleparallel setting, scalar fields have been investigated to a moderate degree, with various extensions having been investigated in the cosmological context [23][24][25][26][27][28]. Furthermore, the effects of the boundary couplings in scalar tensor theories have been discussed in various papers [25,[29][30][31][32][33][34][35][36][37][38][39][40][41]. A recent review on various studies related to dynamical analysis in different cosmological constructions can be found in [42].…”
Section: Introductionmentioning
confidence: 99%
“…As the impetus and implications from fundamental physics to the reasonable form of nonminimal coupling to torsion are still unclear, alternatives to the usual quadratic coupling may be well explored. Of course, there are also proposals for more general scalar-torsion theories including an additional coupling to vector torsion or the boundary term [22,51,84,85], modification of the kinetic term [86], analogue of Horndeski gravity [87], and even more general frameworks [58,63,88]. The current method of investigation should be suitable for those as well.…”
Section: Discussionmentioning
confidence: 99%